Psychiatric morbidity among children and adolescents living in orphanages around Kota Bharu, Kelantan - Ya@Zakaria, Zunaidah (2006)
Background: Child psychiatric morbidity are common and treatable, but often go undetected and therefore remain untreated. Children living in orphanage are more likely to have problems. Objective: To characterize the psychiatric morbidity and associated factors among children and adolescents at risk living in orphanages around Kota Bharu. Method: This study involving two-stage study design. First, screening of all the children and adolescents living in orphanages were done using the Malay version of Strengths and Difficulties Questionnaire. Both of self-rating and teacher-rating were used in this study. In the second stage, all the children and adolescents who were identified as high-risk group (extreme 10 % of population) and selected cases from the low risk group (90% of population) were interviewed for diagnoses using lCD I 0. Results: Based on the SDQ scoring in the screening phase, for the self-rating data, 27 (12%) of children and adolescents scored in the high risk group and 193 (88%) scored in the low risk group, Teacher rating data of SDQ reported that 25 ( 11 %) children and adolescents scored in the high risk group and 195 (88%) scored in the low risk group. In the second stage, for the self rating data 24 (1 0.9%) of respondents had a psychiatric diagnosis and for the teacher rating data, 18 (8.2%) had a psychiatric diagnosis. Conclusions: Psychiatric morbidity were relatively frequent among children and adolescents living in orphanage. This results indicate that increased focus on prevention and early recognition of children and adolescents in need of treatment seems crucial. The screening programmes was found to be useful for the detection of child psychiatric morbidity, thereby improving access to effective treatment.